INOVASI DAN STRATEGI PENCAPAIANNYA - Liem Ferryanto (Institute of Research and Community Outreach - Petra Christian University, 2009)
Innovation is the way of life of any institution to profitably sustain its life. It starts with empathy, the ability to reach outside of ourselves and walk in someone else’s shoes, and optimal implementation of the newly advanced technology. Innovation shows its results through continuously hard working efforts known as